Nilai-nilai Kearifan Lokal Masyarakat Pandalungan: Kasus Upacara Taropan di Probolinggo - Indra Tjahyadi; Hosnol Wafa; Moh. Zamroni (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
This study focuses on the values of the local wisdom of hybrid Probolinggo community. The material object in this study is Taropan Ceremony. Taropan is a tradition carried out by the people of Probolinggo. The method used in this research is ethnographic method through data collection interviews, observations, and literature studies. The results of this study note that Taropan exclusively happens only for the people of Probolinggo. The values of local wisdom in Taropan include (1) the values of brotherhood and (2) the value of religiosity. Overall, it can be seen that the values in Taropan are the fundamental element of the local wisdom values of Probolinggo, especially Pandalungan community that has a hybrid identity which are a mixture of Javanese and Madura wisdom values.